Multi‐Dimensional Molecular Self‐Assembly Strategy for the Construction of Two‐Dimensional Mesoporous Polydiaminopyridine and Carbon Materials. Issue 3 (21st November 2022) - Zhang, Liangliang; Liu, Yumeng; Wang, Tao; Liu, Zhilin; Li, Wei; Qiao, Zhen‐An
Abstract: Two‐dimensional (2D) mesoporous polymers, combining the advantages of organic polymers, porous materials, and 2D materials, have received great attention in adsorption, catalysis, and energy storage. However, the synthesis of 2D mesoporous polymers is not only challenged by the complex 2D structure construction, but also by the low yield and difficulty in controlling the dynamics of the assembly during the generation of mesopores. Herein, a facile multi‐dimensional molecular self‐assembly strategy is reported for the preparation of 2D mesoporous polydiaminopyridines (MPDAPs), which features tunable pore sizes (17–35 nm) and abundant N content up to 18.0 at%. Benefitting from the abundant N sites, 2D nanostructure, and uniform‐large mesopores, the 2D MPDAPs exhibit excellent catalytic performance for the Knoevenagel condensation reaction. After calcination under N2 atmosphere, the obtained 2D N‐doped mesoporous carbon (NMCs) with large and uniform pore sizes, high surface areas, abundant N content (up to 23.1%), and a high ratio of basic N species (57.0% pyridinic N and 35.9% pyrrolic N) can show an excellent CO2 uptake density (11.7 µmol m −2 at 273 K), higher than previously reported porous materials. Abstract : In this study, a facile multi‐dimensional molecular self‐assembly strategy to construct 2D mesoporous polydiaminopyridines and carbon materials is reported. The obtained 2D mesoporous polydiaminopyridines and carbon materials exhibit excellent catalytic activity of Knoevenagel condensation reaction and CO2 uptake density (11.7 µmol m −2 at 273 K) respectively.